Analisis Pengaruh EPS, ROE, DPS dan ROA Terhadap Harga Saham Perusahaan Perdagangan Besar yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2013-2016 - Yang Yang (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study examines the effect of Earning Per Share (EPS), Return On Equity (ROE), Dividend Per Share (DPS) and Return On Asset (ROA) toward Stock Price. This research is used sampling technique is purposive sampling with criteria as follow (1) wholesale company which have go public and active traded in Indonesia Stock Exchange with period 2013-2016;(2) wholesale company that provide annual reports during 2013-2016;(3) wholesale company that still running their business during 2013-2016. Sample was acquired 24 wholesale company that’s fulfill the criteria and this research is using secondary data that’s obtained from www.idx.co.id. The method of analysis used in this research is regression analysis of data panel with the Fixed Effect Model method. The result of this research show that Earning Per Share (EPS), Return On Equity (ROE), and Return On Asset (ROA) partially have not significant effect on stock price of wholesale company while Dividend Per Share (DPS) have significant effect on stock price of wholesale company, however simultaneously have significant effect on stock price of wholesale company. Prediction capability from these variables towards stock price is indicated by adjusted R Squared 96.33% where the residues 3.67% is caused by other factor which not in this research.